1996
DOI: 10.1111/j.1365-2133.1996.tb01151.x
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroid usage and binding to arginine: determinants of corticosteroid hypersensitivity

Abstract: Hypersensitivity to topical corticosteroids is a common cause of allergic contact dermatitis. The development of contact allergy is dependent on individual susceptibility, exposure to the potential allergen and the ability to penetrate the epidermis and react with epidermal protein. We looked at corticosteroid binding to arginine and relative usage of corticosteroids to see if these variables explain the number of allergic reactions seen to these structurally similar chemicals. A linear relationship was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…This suggests that the corticosteroid-glyoxal degradation product is involved in corticosteroid allergy. In vitro, the amount of degradation product, which subsequently reacted with arginine, has been shown to vary between corticosteroids and to be correlated with the frequency of allergic reactions to a steroid (7).…”
mentioning
confidence: 99%
“…This suggests that the corticosteroid-glyoxal degradation product is involved in corticosteroid allergy. In vitro, the amount of degradation product, which subsequently reacted with arginine, has been shown to vary between corticosteroids and to be correlated with the frequency of allergic reactions to a steroid (7).…”
mentioning
confidence: 99%
“…Recent studies suggest that corticosteroids are not allergens themselves; corticosteroids are degraded to a corticosteroid glyoxal that then reacts with arginine molecules of proteins to form the complete antigen; so, the immune system can recognize the allergen [20, 21]. …”
Section: Discussionmentioning
confidence: 99%
“…Other protein-binding mechanisms have been described (106). In thiosteroids such as tixocortol pivalate, which has a thioester group at C21, hydrolysis produces tixocortol which binds rapidly to amino acids such as methionine via a disulphur bridge.…”
Section: Protein Bindingmentioning
confidence: 99%
“…It has been shown that steroid glyoxals can bind to every amino acid except proline and hydroxyproline. The arginine reaction, however, is clearly predominant -and also irreversible (106,107). Wilkinson et al (106) showed that CSs with a greater capacity to bind to arginine do have stronger allergenic properties and recently, Berl et al (107) confirmed that steroids selectively react with arginine to form important adducts.…”
Section: Protein Bindingmentioning
confidence: 99%